Evaluation of epidural detomidine with and without lignocaine and its reversal by atipamezole in Sahiwal calves - Tiwari, S K; Mishra, U K; Mishra, O P (The Indian Journal of Animal Sciences, 2012)
Epidural administration of detomidine (@50µg/kg) with and without hgnocaine (0.22 mg/kg) in 20 healthy Sahiwal calves caused quick onset and longer duration of analgesia (138.00±4 26 versus 90.00±6.45 min) compared to detomidine alone. The transient bradycardia, respiratory depression. ruminal stasis were compensated within 2 hr after administration of drugs. There were nonsignificant changes in haematological profiles. Serum glucose was significanlly (P